Eletromagnetismo: início dos estudos eletromagnéticos e suas aplicações tecnológicas - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2010)
The paper presents the results of an investigation into the history of electromagnetism and its technological applications over the years, reporting the first signs of electricity and magnetism, even to the point where both are related, beginning a new science, the Electromagnetism. Before that discovery, James Clerk Maxwell, he devoted himself for decades to study this relationship and eventually summarized into four equations, later called Maxwell's equations. In parallel to study this new science, there is also the race to develop machines that are related to it. Technologies developed from the study of electromagnetism arose, causing great changes in the way of life of the society, present in all sectors within it, such as transport, communication, health, leisure, education, industry and so on.
Keywords: Eletromagnetismo; Tecnologia; CNPQ::CIENCIAS EXATAS E DA TERRA